Press-klub . Press-klub . Press Club . Пресс-клуб - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. TV-journalists meet and present their work, including material about a Russian citizen taken prisoner by Chechens and transported to Chechnya. Featured in the program: Shchekochikhin, IUrii Petrovich (Journalist); Poltoranin, Mikhail Nikiforovich (Chairman of the Committee for Information Policy and Public Relations of the State Duma of the Russian Federation); Portnikov, Vitalii (Journalist); Venediktov, Aleksei Alekseevich (Journalist); Pavlovskii, Gleb Olegovich (Journalist); Novozhenov, Lev IUr'evich (Journalist); Gerber, Alla Efremovna (Deputy of the State Duma) Contributors: Proshutinskaia, Kira Aleksandrovna (Anchor) Встреча тележурналистов с показом их сюжетов, включая сюжет о гражданине России, захваченным в плен чеченцами и увезенным в Чечню. В программе участвуют: Щекочихин, Юрий Петрович (Журналист); Полторанин, Михаил Никифорович (Председатель Комитета по информационной политике и связям Государственной Думы); Портников, Виталий (Журналист); Венедиктов, Алексей Алексеевич (Журналист); Павловский, Глеб Олегович (Журналист); Новоженов, Лев Юрьевич (Журналист); Гербер, Алла Ефремовна (Депутат Государственной Думы) Создатели: Прошутинская, Кира Александровна (Ведущий/Ведущая)